Creating value(s) by integrating local and extra-local resources in cereal production in the Swiss Alps - Moschitz, Heidrun; Oehen, Bernadette (The International Journal of Sociology of Agriculture and Food, 2020)
This paper explores the long-term prospect of alternative, local food initiatives, taking a particular interest in the development of the embedded local values, understood as economic as well as cultural values. Analysing the case of a cooperative of mountain cereal farmers in Switzerland, we show that sustaining local values-based quality is a dynamic process of linking local and extra-local resources.Our results first show the importance of both proximity and place in constructing the ‘local’ by the cooperative. Second, product flow, knowledge and information exchange, quality control, and innovation are governed by both horizontal and vertical relationships between local and extra-local resources, and these multiple relationships build trust in the network and beyond.This, thirdly, enables the cooperative to continuously reproduce its values by weaving them into a cycle of quality creation. We conclude that we need to understand the characteristic values-based quality of the cooperative’s products as the result of a recurring cycle of local and extra-local knowledge creation and resource exchange. Key words: local; extra-local; value chains; values; proximity; place; rural development;